Perancangan Mesin Pengisi Cairan pada Botol Otomatis Dua Mode menggunakan Metode FEA - Wistikhirana, Hanandira; Rahman, Fio Izzafur; Kaunang, Revo Alfian; Nabil, Muhammad; Muslimin, Muslimin; Luqyana, Dhiya; Muhamad, Azam Milah (Manutech : Jurnal Teknologi Manufaktur, 2025)
This study examines the design and safety analysis of an automatic liquid filling machine for bottles with two modes: 250 ml and 500 ml. The problem addressed is the time-consuming and inconsistent manual bottle filling process in UMKM. The machine is designed to improve efficiency and consistency in filling liquids for UMKM. Made from PLA filament using 3D printing, the machine has dimensions of 400 mm x 350 mm x 350 mm and was analyzed using Finite Element Analysis (FEA). The load on the machine is 2.4516625 N for 250 ml and 4.903325 N for 500 ml. Simulation results show a maximum stress of 0.114 N/mm² for 250 ml and 0.118 N/mm² for 500 ml, both below the PLA material's yield strength of 26,082 N/mm². The maximum displacement is 0.002 mm for 250 ml and 0.00894819 mm for 500 ml. The minimum safety factor is 4,044e+02 for 250 ml and 1,156e+02 for 500 ml. These results confirm that the machine design is safe and reliable for automatic liquid filling in both modes.